Experimental analysis of ecuadorian adobe reinforced with natural fibers - Pinto-Almeida, Carlos; Jordán-Buenaño, Nancy; Armas-Robalino, Nahomy Anahí; Cáceres, Bianca Christina; Cajas-Corrales, Juan Carlos; Medina-Medina, Ronald Steeven; Buele, Jorge (Frontiers in Built Environment, 2025)
IntroductionIn Latin America, the use of adobe as a building material remains highly relevant due to its low cost, local availability, and low environmental impact. Nevertheless, its limited mechanical strength and lack of standardization constrain broader implementation in contemporary architecture.MethodsThis study addresses that gap by experimentally evaluating the mechanical performance of adobe blocks stabilized with fine sand and wild straw, produced with red clay from Puyo (Ecuador). The research followed an applied, descriptive–comparative design encompassing material characterization, a 30-day natural curing process, and compressive strength testing using a SHIMADZU Concreto 2000X machine.ResultsThe stabilized blocks achieved an average compressive strength of 9.63 kg/cm² (≈ 0.94 MPa), a mean displacement of 2.98 mm, and a maximum load of 14.16 kN, values that confirm their suitability for low-rise load-bearing structures. The inclusion of wild straw improved ductility, internal cohesion, and post-fracture integrity, while controlled shade drying minimized microcracking. Compared with traditional handmade bricks (31 kg/cm²), the material showed lower strength but significantly higher environmental and economic sustainability.ConclusionThe results provide empirical indicators to guide the standardization and scalability of stabilized adobe as a low-carbon, structurally viable alternative for rural and peri-urban housing in seismic regions.